2001
DOI: 10.1037/0033-3204.38.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder patients' readiness to change alcohol and anger problems.

Abstract: Recovery from combat-related Posttraumatic Stress Disorder (PTSD) is often complicated by unacknowledged problems with alcohol and anger. Male combat veterans fn = 702) entering a residential PTSD rehabilitation program completed University of Rhode Island Change Assessment (URICA) and process-of-change questionnaires based on Prochaska and DiClemente's transtheoretical model (TTM; Prochaska, DiClemente, & Norcross,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Most of the research that has been used to support the TTM comes from the addiction and health-related behavior fields. Only four studies thus far have examined the applicability of the TTM to trauma survivors and even these have not fully examined the assumptions of the TTM (Boyd, unpublished doctoral dissertation; Gewirtz, unpublished doctoral dissertation; Koraleski & Larson, 1997;Rosen et al, 2001). The current study is therefore directed towards evaluating the application of this model to a PTSD veteran population.…”
Section: Decisional Balance (Db)mentioning
confidence: 94%
See 1 more Smart Citation
“…Most of the research that has been used to support the TTM comes from the addiction and health-related behavior fields. Only four studies thus far have examined the applicability of the TTM to trauma survivors and even these have not fully examined the assumptions of the TTM (Boyd, unpublished doctoral dissertation; Gewirtz, unpublished doctoral dissertation; Koraleski & Larson, 1997;Rosen et al, 2001). The current study is therefore directed towards evaluating the application of this model to a PTSD veteran population.…”
Section: Decisional Balance (Db)mentioning
confidence: 94%
“…Boyd (unpublished doctoral dissertation) found that adult female trauma survivors at entry to treatment highly endorsed items assessing the contemplation SOC. Furthermore, Rosen et al (2001) found that at entry to treatment between 18 and 25% of their PTSD sample were in the precontemplation SOC for the assessed areas (i.e. anger and alcohol).…”
Section: Stages Of Change (Socs)mentioning
confidence: 98%
“…Despite this evidence, there is a lack of research examining this association among individuals with SUD. Some studies have demonstrated that PTSD is significantly associated with elevated levels of anger and difficulties managing anger among individuals with alcohol use disorder (Elbogen et al, 2010;Jakupcak et al, 2007;Rosen et al, 2001). These studies, however, are generally limited to samples of male combat veterans who misuse alcohol.…”
Section: Anger Among Individuals With Sudmentioning
confidence: 97%
“…One study applying the model to Vietnam veterans with PTSD and their readiness to change alcohol use and anger (Rosen et al, 2001) found that veterans with PTSD varied in their readiness to change, and that readiness to change was unrelated to PTSD symptom severity. To date, there has been no evaluation of a stages of change model in veterans with PTSD returning from Iraq and Afghanistan, and since this group is typically younger and may be more likely to use VA services (Seal, Bertenthal, Miner, Sens, & Marmar, 2007) it may be useful to evaluate the stages of change model in this cohort.…”
Section: Introductionmentioning
confidence: 99%